2007
DOI: 10.1007/s10551-006-9249-4
|View full text |Cite
|
Sign up to set email alerts
|

The International Business Ethics Index: European Union

Abstract: business ethics, consumer sentiments, business ethics index (BEI), UK, Germany, Spain,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Additionally, the cultural, moral and ethical values could be alike in different countries; but, the implementation of these issues might vary. Therefore, the best course to adjust indigenous ethical and cultural standards is to adopt a contingency inclination on the cultural, morale, historical and individual basis rather than a universal point of view in order to influence ethical conduct positively (Tsalikis, Seaton, 2007;Tsalikis et al, 2008;Helin, Sandström, 2008).…”
Section: Ethical Issues In International Businessmentioning
confidence: 99%
“…Additionally, the cultural, moral and ethical values could be alike in different countries; but, the implementation of these issues might vary. Therefore, the best course to adjust indigenous ethical and cultural standards is to adopt a contingency inclination on the cultural, morale, historical and individual basis rather than a universal point of view in order to influence ethical conduct positively (Tsalikis, Seaton, 2007;Tsalikis et al, 2008;Helin, Sandström, 2008).…”
Section: Ethical Issues In International Businessmentioning
confidence: 99%
“…A BEI Component score was calculated for each of the four BEI components (see Tsalikis and Seaton, 2007b). For comparison reasons, along with the results for Japan, China, India, and the 2006 U.S. BEIs are also presented in Table II.…”
Section: Analysis Of the Individual Index Componentsmentioning
confidence: 99%
“…After the initial measurements of the BEI in 2004 and 2006 in the United States of America, the BEI was expanded to the European Union (U.K., Spain, and Germany - Tsalikis and Seaton, 2007b), and the two emerging economies of Asia (China and India - Tsalikis et al, 2007c). The present paper will expand the BEI measurement to a major economic power -Japan.…”
Section: Introductionmentioning
confidence: 97%
“…The revelation of several major scandals in leading German corporations (e.g., Deutsche Bank, Volkswagen, and Siemens) has shown that there are problems in the realm of business ethics. Recent internationally comparative research on business ethics revealed that German respondents have become particularly pessimistic about the likelihood of corporations acting responsibly in future (Tsalikis and Seaton, 2007). More generally, at least three interrelated processes are undermining the country's ability to maintain and develop high standards.…”
Section: Introductionmentioning
confidence: 99%